Factors affecting breeding soundness classification of beef bulls examined at the Western College of Veterinary Medicine - Barth, Albert D. (2002)
Breeding soundness evaluation records from 2110 beef bulls, for the period of 1986 to 1999, were analyzed to determine the prevalence and importance of factors affecting breeding soundness classification. The percentage of all bulls classified as satisfactory ranged from 49.0% in January to 73.3% in May. The percentage of physically normal bulls with satisfactory semen quality ranged from 65.7% in January to 87.5% in June. Poor body condition or excessive body condition, below average or below the recommended minimum scrotal circumference, lameness, and severe scrotal frostbite significantly reduced the probability of a satisfactory breeding soundness classification. The percentage of sperm with midpiece defects declined significantly and the percentage of sperm with head defects increased significantly with the approach of summer. Photoperiod, cold stress, poor or excessive body condition, and reduced feed quality may interact to reduce semen quality in the winter months.